Optical Dating of Modern and Late Holocene Dune Sands in the Brandon Sand Hills, Southwestern Manitoba - Wolfe, Stephen; Huntley, David; Ollerhead, Jeff (Géographie physique et Quaternaire, 2002)
AbstractFor any suite of optical dating samples two issues that must be considered are: do zero-age samples yield an optical age of zero, and are the optical ages consistent with independent stratigraphic and chronologic information? A test of the zero-age of dune sands was performed by dating samples from the crest, lee slope and stoss slope of an active dune in southwestern Manitoba. Three surface samples showed that, using 1.4 eV (infrared) excitation of K-feldspars, the equivalent dose, and hence “age”, depended on whether the bleach used for the thermal transfer correction was infrared/red or sunlight, leading to an age uncertainty of about ±40 years. Optical ages for samples 50 cm below these, and calculated relative to them, were 8 ± 8, 1 ± 7, and 38 ± 7 years, independent of the bleach used. These ages are consistent with expectations for the crest, lee slope and stoss slope, respectively. Optical ages of late Holocene dune sand units at the Brookdale Road section, southwestern Manitoba, were consistent with radiocarbon ages from organic matter within intervening buried soils. The suite of optical and radiocarbon ages from the Brandon Sand Hills provides a record of dune activity and stability for the region, and tentatively identifies periods of eolian activity at about 2 ka, 3.1 to 4.0 ka, and prior to 5.2 ka.